Porter’s Analysis as a Standardized Process Applicable in Industrial Companies - Kozel, Roman; Mikolas, Milan; Vilamova, Sarka; Chuchrova, Katerina; Piecha, Marian (Communications - Scientific letters of the University of Zilina, 2016)
Reliability and safety of energy, drinking water deliveries and draining wastewater from built- up areas in cities and villages have many proportions and technical-operational conditions. Among basic requirements of the use of all types of residential or manufacturing objects in the 21st century is reliable delivery of drinking water, draining and cleaning of urban and industrial sewage. Disturbance or putting out of service of this type of infrastructure has always a domino effect. Gradually growing reliance of user base of all types of drinking water consumers leads especially in the section of the public or private infrastructure to restriction or complete stoppage of their operation. The following article defines in basic range the ways and means how to lower the danger that an emergency situation in operational systems of drinking water will be unmanageable and how to prevent natural or anthropogenic threats at the particular type of technical infrastructure.